COMMUNITY SERVICE THROUGH THE TRAINING PROGRAM “THE END & RISE OF BOARD GAME” AT SMA NEGERI 3 SEMARANG AND DHADHU BOARD GAME SEMARANG - Setyo Budi; Indra Gamayanto; Sasono Wibowo; Budi Widjajanto; Achmad Wahid Kurniawan; Hanny Haryanto; Aries Setiawan (Universitas Airlangga, 2025)
This community service program aimed to provide training on the utilization of board games as a learning medium at SMA Negeri 3 Semarang in collaboration with Dhadhu Board Game Café. The implementation methods included needs analysis, material preparation, training sessions, and evaluation using questionnaires. A total of 40 students participated in the program. The evaluation results showed that 75% of participants understood the concept and benefits of board games, 60% considered board games helpful in enhancing analytical skills, and 70% reported improved self-confidence and teamwork ability. The tangible impact of this activity was an increased awareness among students of the potential of board games as an interactive and engaging alternative learning medium. Practically, this program provides implications for teachers to integrate board games into classroom learning and opens opportunities for further research on long-term effectiveness.